G Protein Subunit Beta 3 (GNB3) Variant Is Associated with Biochemical Changes in Brazilian Patients with Hypertension - Agostini, Lívia da Cunha; Silva, Nayara Nascimento Toledo; Lopes, Ana Cláudia Faria; Melo, André Sacramento; Bicalho, Luciana Soares Moreira; Almeida, Tamires Cunha; Belo, Vanessa de Almeida; Coura-Vital, Wendel; Teixeira, Luiz Fernando de Medeiros; Lima, Angélica Alves; Silva, Glenda Nicioli da (Arquivos brasileiros de cardiologia, 2023)
Central Illustration : G Protein Subunit Beta 3 (GNB3) Variant Is Associated with Biochemical Changes in Brazilian Patients with Hypertension. Genes and their variants associated with environmental factors contribute to the development of the hypertensive phenotype. The G protein beta 3 subunit gene (GNB3) is involved in the intracellular signaling process, and its variants have been related to susceptibility to arterial hypertension. To determine the association of the GNB3 variant (rs5443:C>T) with arterial hypertension, biochemical parameters, age, and obesity in hypertensive and normotensive individuals from Ouro Preto, Minas Gerais, Brazil. The identification of variants was performed by real-time PCR, using the TaqMan® system, in 310 samples (155 hypertensive and 155 normotensive). Biochemical analyses (renal function, lipid profile and glycemia) were performed from the serum using UV/Vis spectrophotometry and ion-selective electrode. A multiple logistic regression model was used to identify factors associated with arterial hypertension. The analysis of continuous variables with normal distribution was performed using the unpaired Student's t test; non-normal data were analyzed using Mann-Whitney. P < 0.05 was considered significant. The rs5443:C>T variant was not associated with arterial hypertension in the evaluated population (p = 0.88). Regarding biochemical measures, the T allele was associated with high levels of triglycerides, glucose and uric acid in hypertensive individuals (p < 0.05). These results show the importance of genetic diagnosis to prevent the causes and consequences of diseases and imply that the GNB3 rs5443:C>T variant may be associated with changes in the biochemical profile in hypertensive individuals.